Bismuth subsalicylate as potential treatment for Covid-19 pneumonia: A case series report - Kahlenborn, Chris; Severs, Walter B.; Nawab, Khalid (Frontiers in Drug Discovery, 2022)
Various literature cited suggests that bismuth may have usefulness against Covid-19 both in vitro and in vivo. During the course of caring for Covid-19 patients we administered bismuth subsalicylate to those who displayed diarrhea and/or gastric complaints. Using relatively conservative criteria, we noted marked improvement in oxygen requirements in most of the cases. This improvement was observed even when prior therapy with standard anti-Covid drugs had failed. Our overall impression is that these positive results support a detailed evaluation of bismuth as an adjunct treatment for the treatment of Covid-19.